WebFlow - a visual programming paradigm for Web/Java based coarse grain distributed computing - Bhatia, Dimple; Burzevski, Vanco; Camuseva, Maja; Fox, Geoffrey; Furmanski, Wojtek; Premchandran, Girish (Concurrency (Chichester, England.), 1997)
We present here recent work at NPAC aimed at developing WebFlow – a general purpose Web‐based visual interactive programming environment for coarse grain distributed computing. We follow the 3‐tier architecture with the central control and integration WebVM layer in tier‐2, interacting with the visual graph editor applets in tier‐1 (front‐end) and the legacy systems in tier‐3. WebVM is given by a mesh of Java Web servers such as Jeeves from JavaSoft or Jigsaw from MIT/W3C. All system control structures are implemented as URL‐addressable servlets which enable Web browser‐based authoring, monitoring, publication, documentation and software distribution tools for distributed computing. We view WebFlow/WEbVM as a promising programming paradigm and co‐ordination model for the exploding volume of Web/Java software, and we illustrate it in a set of ongoing application development activities. © 1997 John Wiley & Sons, Ltd.